2022
DOI: 10.1021/acs.jmedchem.1c01485
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Antimicrobial Peptide with Selective Killing Activity for Bacterial Abscess Therapy

Abstract: The unusual acidic pH of the abscess milieu is an adverse factor that decreases the therapeutic efficacy of traditional antibiotics. Moreover, avoiding both the undesired killing of commensal bacteria and the development of drug resistance remains difficult during abscess therapy. Hence, we synthesized a series of pH-responsive antimicrobial peptides equipped with efficient bacterial killing activity at pH 6.5 and inactivity at pH 7.4. Among the peptides, F5 exhibited outstanding pH-responsive antimicrobial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…As shown in Figure 3D, the bactericidal action of WL-C 6 was rapid, and is similar to that observed for many AMPs, indicating that WL-C 6 may adopt a similar membrane-disruptive mechanism of action (Song et al, 2019;Chou et al, 2021;Wang et al, 2022). Therefore, in order to gain a preliminary understanding of the WL-C 6 action site, we conducted super-resolution fluorescence imaging using 3D structured illumination microscopy (3D-SIM) to monitor the localization site of WL-C 6 in E. coli.…”
Section: Preliminary Mechanistic Studiessupporting
confidence: 73%
See 1 more Smart Citation
“…As shown in Figure 3D, the bactericidal action of WL-C 6 was rapid, and is similar to that observed for many AMPs, indicating that WL-C 6 may adopt a similar membrane-disruptive mechanism of action (Song et al, 2019;Chou et al, 2021;Wang et al, 2022). Therefore, in order to gain a preliminary understanding of the WL-C 6 action site, we conducted super-resolution fluorescence imaging using 3D structured illumination microscopy (3D-SIM) to monitor the localization site of WL-C 6 in E. coli.…”
Section: Preliminary Mechanistic Studiessupporting
confidence: 73%
“…AMPs are small molecular active peptides and have been widely isolated and characterized from animals, plants, bacteria, fungi, protists, and archaea (Wang et al, 2016). Different AMPs show different biological functions, such as antibacterial (Shao et al, 2021;Panteleev et al, 2022;Wang et al, 2022), antibiofilm (Zai et al, 2021), antivirals (Ji et al, 2018), antifungal (Chou et al, 2021), anticancer and immunomodulatory (Lugo et al, 2019;Mookherjee et al, 2020). More than 22,400 AMPs have been isolated from nature or created synthetically in the lab as of this writing (Shi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Activity screening and stability assays showed that the half-life of the analog DR3penA in serum was prolonged from 70.19 ± 6.83 to 174.63 ± 31.66 min and that the effective concentration of DR3penA was reduced from 80 to 2.5 μmol/L in vitro . We speculated that the quaternary carbon structure and long hydrophobic fatty chain of α -(4-pentenyl)-Ala improved the stability of the peptide and thar the enhanced hydrophobicity of DR3penA may increase the antioxidant activity of the peptide and promote the entry of the peptide into cells 34 , 43 , 44 . To prove this hypothesis, we compared the ROS-scavenging ability of DR8 and DR3penA in A549 cells and NIH3T3 cells using DCFH-DA fluorescent probe.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the relationship between charge and antibacterial activity of these new T-PE analogues, the introduction of Glu acid would lead to the decrease of the hemolytic activity. The possible reasons were as follows: (i) the γ-carboxyl group of Glu will introduce a negative charge, reducing the hydrophobicity of AMPs and interrupting the continuity of the charge on the hydrophilic surface; , (ii) the helical structure of the new AMP could be influenced by the side-chain charge interactions; , and (iii) the negative charge of the Glu residue prevents the peptide from interacting with the negatively charged phosphoryl group of cell membrane phospholipids . Moreover, the addition of Lys would reduce the hydrophobicity of the peptide and also provide positive charge.…”
Section: Resultsmentioning
confidence: 99%